Identify the consumption patterns of the second generation Chinese middle class. Does culture influence their consumption habits? - Liu, Kim Man (2012)
Background: The 1978 political social reform in China has led to the emergence of the rapid and fast growing urban ‘middle class’ population. With the rise of the large population of middle class consumers, global market developers and opportunists are targeting this group of people to maximize their profits in developing countries. This research aimed to identify the consumption patterns of the second generation Chinese middle class and to investigate if their unique Chinese culture influenced their consumption habits. Methods: This qualitative research was conducted through semi-structured, in-depth interviews with 15 Chinese participants that were previously selected based on three pre-determined criteria. The interviews were conducted at the participants’ houses and through Skype sessions, where the researcher further developed his questions during the interview process based on observations made from their surroundings. Results: The empirical data indicated that the main concern of the second generation Chinese middle class when selecting universities was the ranking and reputation of the university, not the educational expenses. Their food expenditures consisted of grocery shopping for ready-made meals and oriental products and eating out. The participants considered treating someone to dinner a way to build up social connections, ‘guanxi’. Furthermore, their leisure expenditures were supplemented by the extra amount of allowance they had. Social connection was considered an important element within the Chinese culture to climb up the social ladder in terms of status and career development which indirectly influenced their consumption patterns. Conclusion: To conclude, the Chinese middle class willingness to spend a large amount of money on educational expenses signify a strong link between education and better job prospects or a better future, in general. Furthermore, their unique culture influences such as inheritance of home ownership and ‘guanxi’ influenced their consumption patterns.